Effects of density and resin level on the permeability and water absorption of kenaf-rubberwood particleboard - Abdul Halip, Juliana; Md. Tahir, Paridah; Choo, Adrian Cheng Yong; Mazraehshahi, Alinaghi Karimi (Indonesian Wood Research Society, 2014)
The aim of this study was to evaluate the effect of board density and resin level on the permeability and water absorption of particleboard made from rubberwood-kenaf blends. Kenaf whole stem particles were mixed with rubberwood particles at a ratio of 50:50 (w/w) to produce particleboards with three different densities (300, 500, and 700 kg/m3) and urea formaldehyde (UF) resin levels (6, 8, and 10%). Results show that the density and resin levels had significant effects on the permeability and water absorption of the particleboards: increased densities and resin levels resulted in lower permeability and water absorption. A clear relationship between the permeability and physical properties of particleboard was also discovered, where the decrease of permeability in the boards also caused lower water absorption values. Boards with low density were observed to have more voids and less compactness that may facilitate the penetration of water.